Caracterização ambiental da paisagem urbana de Erechim e do Parque Municipal Longines Malinowski. Erechim - RS - Zanin, Elisabete Maria (2002)
It was carried out the analysis and the environmental characterization of the urban area as a subsidy to the review of the Urban Development Directive Plan of the municipality of Erechim (Rio Grande do Sul, Brazil), associated with a combined proposal of the environmental zoning and the conceptual management plan of Parque Municipal Longines Malinowski (PMLM), one of the structural-natural elements in the urban landscape, directing the development of actions related to the use and maintenance of this Urban Ppark, in the perspective to ensure the environmental and life quality of the city of Erechim. PMLM comprises a fragment of mixed ombrophilic forest, totally limited by an urban contour. The environmental analysis was made with the use of SIG-IDRISI with structural elements of the urban landscape and of PMLM, resulting in hypsometric, clinographic, hydrographic and soil use and occupation thematic maps. The altimetry variation was of 45 m of altitude for PMLM and of 210 m for the urban area. The city of Erechim presented an green area ratio (IAV) of 3.72 m2/inhabitant, being PMLM responsible for 46.50% of that. Fourteen types of soil use and occupation of for PMLM were identified, with the predominance of the ombrophilic forest in which (Bert.) Kuntze, Mart. ex Reiis.llex dumosa Reiis are found and are described in the list of endangered species. Based on the thematic maps and the creation law, a proposal for the environmental zoning and immediate contour of PMLM were made, as well as a conceptual management plan with 7 programs and 18 subprograms. PMLM presents a great potential for the practice of local biodiversity conservation. The decision-making concerning the use and occupation of its space, in the perspective of its conservation and continuity in the urban landscape, involves the consideration of the environmental zoning and the dynamics of the Park and its surroundin use and occupation of the. Any initiative to improve the environmental quality of PMLM will depend necessarily on the involvement and participation of the community.